Pengaruh Budaya Isap Buyu dalam Kepercayaan Masyarakat Kalimantan Selatan Terhadap Risiko Terjadinya Gizi Buruk Balita: The Influence of the Buyu Sucking Culture in the Beliefs of the People of South Kalimantan on the Risk of Malnutrition in Toddlers - Gusti Viana Fadhina Ulfah; Sary, Raida Athaya Sary; Agus Salim; Sri Wahyuni; Muhammad Irwan Setiawan (UNIVERSITAS NGUDI WALUYO, 2026)
Data Data from the World Health Organization (WHO) in 2022 shows that Indonesia ranks second in terms of the highest number of malnutrition cases among 84 countries, with a total of 812,564 infants. In South Kalimantan, based on 2020 data, the prevalence of stunting reached 11.9% and underweight infants reached 6.5%. The highest prevalence of underweight infants was found in Banjar District at 10.9%, while the highest prevalence of malnutrition reached 14.5%. Isap Buyu is a term in the beliefs of the South Kalimantan community referring to the condition of underweight infants who have difficulty gaining weight and face developmental delays. Isap Buyu is believed to be a disease caused by disturbances from supernatural beings, so its treatment often involves traditional Isap Buyu rituals. This study aims to analyze the relationship between belief in Isap Buyu and the occurrence of malnutrition in infants. The study uses a qualitative method with semi-structured interviews with four informants selected through purposive sampling. Data analysis was conducted through reduction, presentation, and drawing conclusions. The results of the study indicate a relationship between community beliefs about Isap Buyu and an increased risk of malnutrition in infants. These beliefs lead the community to prefer traditional treatments over healthcare services, which may worsen the infants' condition. Additionally, factors such as breastfeeding, dietary patterns, and the presence of comorbidities also contribute to the occurrence of malnutrition. ABSTRAK Data World Health Organization (WHO) tahun 2022 mencatat Indonesia menempati urutan kedua kasus gizi buruk tertinggi dari 84 negara dengan jumlah 812.564 balita. Di Kalimantan Selatan, berdasarkan data tahun 2020 prevalensi stunting mencapai 11,9% dan balita kurus 6,5%. Kasus tertinggi balita kurus ditemukan di Kabupaten Banjar sebesar 10,9%, sedangkan kasus gizi kurang tertinggi mencapai 14,5%. Isap Buyu merupakan istilah dalam kepercayaan masyarakat Kalimantan Selatan yang merujuk pada kondisi balita kurus, sulit gemuk dan mengalami hambatan dalam tumbuh kembang. Isap Buyu dipercaya sebagai penyakit akibat gangguan makhluk halus, sehingga penanganannya sering dilakukan dengan ritual tradisional Isap Buyu. Penelitian ini bertujuan menganalisis hubungan kepercayaan terhadap Isap Buyu dengan kejadian gizi buruk pada balita. Penelitian menggunakan metode kualitatif dengan wawancara semi terstruktur terhadap 4 orang informan yang dipilih melalui teknik purposive sampling. Analisis data dilakukan melalui reduksi, penyajian dan penarikan kesimpulan. Hasil penelitian menunjukkan adanya hubungan antara kepercayaan masyarakat terhadap Isap Buyu dan meningkatnya risiko gizi buruk pada balita. Kepercayaan tersebut membuat masyarakat cenderung lebih memilih pengobatan tradisional dibandingkan layanan kesehatan yang dapat memperburuk kondisi balita. Selain itu, faktor pemberian ASI, pola asupan makanan, serta adanya penyakit penyerta juga turut berkontribusi terhadap terjadinya gizi buruk.